Pharmacogenetic-guided and clinical warfarin dosing algorithm assessments with bleeding outcomes risk-stratified by genetic and covariate subgroups. (15th October 2020) - Dietz, Nicholas; Ruff, Christian; Giugliano, Robert P.; Mercuri, Michele F.; Antman, Elliott M.
Abstract: Background: Safe administration of warfarin presents challenges due to a narrow therapeutic INR range and significant variability in inter-individual dose response. Bleeding secondary to warfarin use is a leading cause of hospitalization. Methods: Five warfarin dosing algorithms were assessed for accuracy of predicted compared to the INR target dose for patients with a HAS-BLED score ≥3 participating in the ENGAGE-AF TIMI 48 trial. Three warfarin metabolism subgroups (normal, sensitive, and highly sensitive responders) were established based on genotype. Mean differences between calculated and prescribed dose were determined for each algorithm across groups. Results: A total of 7036 patients were analyzed and 1846 participants with HAS-BLED ≥3 were genotyped. The mean absolute error of predicted versus INR target dose for warfarin ranged from 8.1 mg/week on the pharmacogenetic-guided International Warfarin Pharmacogenetics Consortium (IWPC) and Gage algorithms to 11.3 mg/week on fixed dose. Overestimation of INR target dose occurred in 98% of highly sensitive responders by 21 mg/week for subjects on fixed dose. Pharmacogenetic-guided IWPC saw 89% overestimation with mean difference of 8.3 mg/week for highly sensitive responders. Major or clinically relevant non-major bleeding in the first 90 days of beginning warfarin was 3.27 times more likely for highly sensitive than normal responders. Conclusions: Initial doses were higher than INR target doses in high-risk bleeding subpopulations as defined by the modified HAS-BLED and genotype sensitivity analysis when compared to established algorithms. Clinical and pharmacogenetic-guided algorithms improved dosing in highly sensitive responders with HAS-BLED ≥3 compared to fixed dosing. Highlights: Narrow therapeutic INR range and dose variability challenges safe warfarin use. Sensitive responders with modified HAS-BLED ≥3 had 2 mg/day higher on fixed dose. Pharmacogenetic Gage and IWPC algorithms had best prediction performance. Clinical and pharmacogenetic algorithms improved dosing accuracy by 8–9 mg/week. Bleeding events were most likely to occur in the first 90 days of treatment onset.